Comparison of muscle activity in lower extremities between high jumpers and general athletes during running single-leg vertical jump over different distances - Hsu, T. M.; Huang, B. X.; Nai, H. F.; Lin, J. Z. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The running vertical jump is a common action on sports fields, and most running vertical jump applies single-foot takeoff [1]. With special training, horizontal kinetic energy can be effectively converted into vertical kinetic energy. The speed of the approach run affects jumping performance, which is affected by the running distance. Therefore, the ideal jumping performance requires a balance between the vertical jump and the speed of the approach run. However, the differences regarding muscles and the speed of the approach run between professional athletes of jumping events and general athletes have rarely been discussed. The aim in this study was to determine how different approach run lengths affect single-leg vertical jumps. The jumping performance and characteristics of lower limb muscle activation of professional and general athletes were observed.